Perputaran Perputaran Modal Kerja, Likuiditas dan Leverage, Memacu Rentabilitas Perusahaan - Edwin Agus Buniarto (Universitas Islam Kadiri, 2021)
Abstract This study aims to determine the effect of working capital turnover, liquidity and solvency on profitability in food and beverage sub-sector companies in the Indonesian Capital Market for the 2016-2020 period. Working capital turnover variable is calculated using the Working Capital Turnover ratio, liquidity is measured using Current Ratio, solvency is measured using Debt to Assets Ratio and Profitability is measured using Return on Assets. This type of research is quantitative using the classic assumption test, multiple linear regression analysis and partial test. The sampling technique uses the purposive sampling method. The results of the analysis that have been done, show that the working capital turnover, liquidity and solvency significantly influence the profitability of the company. This is evidenced by the results of correlation analysis which shows the value of r = 0.831 which means there is a strong relationship between working capital turnover, liquidity and solvency to profitability. Partially, each independent variable significantly influences profitability. Keywords: Working Capital Turnover, Liquidity, Solvency, Return on Assets